2020
DOI: 10.1111/irj.12282
|View full text |Cite
|
Sign up to set email alerts
|

Deregulation and institutional conversion in the Greek hotel industry: an employment relations model in transition

Abstract: Before the debt crisis of 2010 forced Greece into almost permanent austerity, its hotel workers enjoyed wages and conditions (through a sector collective agreement) similar to those in other economic sectors. This was against the international trend where low wages and poor conditions were standard. Sweeping deregulation by Greek governments has brought much of the hotel industry into line with other countries. The sector agreement, now covering a much smaller proportion of the workforce, survived but has expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 29 publications
0
11
0
1
Order By: Relevance
“…The latter exacerbates the individualisation of the employment relationship and makes it hard for the model of individual complaints and grievances to help workers defend and exercise their rights. As previous research has indicated (see Papadopoulos & Lyddon, 2020), a strong workplace union presence can enable hospitality unions to put pressure on employers to decelerate their offensive on employment rights and on the State to strengthen the enforcement mechanisms. A stronger union presence in the UK hospitality industry could support workers to break their 'silence' by reducing the high levels of isolation/fear and growing their confidence to seek information, recognise and defend their labour rights.…”
Section: Discussionmentioning
confidence: 97%
“…The latter exacerbates the individualisation of the employment relationship and makes it hard for the model of individual complaints and grievances to help workers defend and exercise their rights. As previous research has indicated (see Papadopoulos & Lyddon, 2020), a strong workplace union presence can enable hospitality unions to put pressure on employers to decelerate their offensive on employment rights and on the State to strengthen the enforcement mechanisms. A stronger union presence in the UK hospitality industry could support workers to break their 'silence' by reducing the high levels of isolation/fear and growing their confidence to seek information, recognise and defend their labour rights.…”
Section: Discussionmentioning
confidence: 97%
“…Certain features of the hospitality sector combine to offer a partial explanation of why union membership levels are especially low there, including the prevalence of young workers, seasonal fluctuations in demand, the transient nature of employment and the smallness of the vast majority of employers. That said, comparison with other countries, where union membership and collective bargaining coverage in hospitality are much higher, suggests that there is nothing inevitable about this (Ioannou, 2015;Papadopoulos & Lyddon, 2020). 1 While recruiting young, precariously employed workers is a difficult task, there is increasing willingness on the part of trade unions to devote resources to this, engaging in innovative organising efforts to address young workers' interests (Simms et al, 2018).…”
Section: A Transient Workforcementioning
confidence: 97%
“…The tourism and hospitality industry has been linked with poor working conditions, high turnover and menial work, so the scope and incentives for learning initiatives in this sector are less developed, although policy makers and employers insist that the right occupational skills and qualifications can help them secure decent employment in the sector (Papadopoulos & Lyddon, 2020).…”
Section: Theoretical Frameworkmentioning
confidence: 99%